Land use and land cover changes and their effect on ecosystem service values in the Bale Ecoregion, southeastern Ethiopia - Haileslassie, Amare; Taye, Meron Teferi; Diyessa, M.; Mekuria, Wolde (Frontiers Media, 2024)
The Bale Ecoregion (BER) is known for its global importance in biodiversity and as a water tower for East African drylands. Land use and land covers (LULC) have been changing for decades, affecting forest ecosystem service values (ESVs), but available information is limited. The present study addresses these gaps by using contrasting watersheds representing the highland, midland, and lowland agroecologies in the BER. LULC classifications were performed using GIS and remote sensing tools. Multisite imagery data (using Landsat image resolution 30 m × 30 m) were generated for four observation periods: 1992, 2002, 2012, and 2022. A recently updated global ESV coefficient and the value transfer valuation method were applied to estimate the changes in ESVs related to LULC changes. The result demonstrates that between 1992 and 2022, forest land has decreased by 3%, 63%, and 22% in the highland, midland, and lowland areas, respectively. Different degrees of loss of ESVs were observed across the study periods and LULC. Of the 21 specific ESVs investigated, the highest annual losses were recorded for water ecosystem services both in the midland and lowland landscape positions. Increased ESVs for cultivated land could not offset losses in food ESVs at the scale of agroecology. Significant impacts of LULC changes on specific ecosystem services, such as water, and changes in natural connectivity between the highland and lowland areas were observed. The result suggests that stakeholders need to co-plan and manage the BER. This evidence provides a scientific underpinning for understanding the connection between LULC change and ESVs and supports informed policy decisions.